2011
DOI: 10.1063/1.3571494
|View full text |Cite
|
Sign up to set email alerts
|

Short-time pressure response during the start-up of a constant-rate production of a high pressure gas well

Abstract: The start-up flow of a constant-rate production of a high pressure gas well is studied, with emphasis on the effect of gas acceleration. Gas acceleration is important in the near wellbore region for a high pressure gas in a high permeability formation. It is shown that when gas acceleration is important, the system of governing equations for the porous media flow becomes hyperbolic. In response to an impulsively imposed mass flow-rate, a steep pressure front is created at the wellbore and it propagates into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…During exploitation of high-temperature, high-pressure and high-production gas wells, fluid flow rate in tubing string is high. In addition to well opening and shut-in conditions (Han et al, 2012;Jin et al, 2011), the different geological conditions of different regions will affect the production of gas well (Zhang et al, 2020a). If the fluid flow rate in tubing string changes significantly for certain factors and results in momentum conversion in these conditions, violent pressure fluctuations will be caused in tubing string (Li et al, 2013).…”
Section: Symbol Annotationsmentioning
confidence: 99%
“…During exploitation of high-temperature, high-pressure and high-production gas wells, fluid flow rate in tubing string is high. In addition to well opening and shut-in conditions (Han et al, 2012;Jin et al, 2011), the different geological conditions of different regions will affect the production of gas well (Zhang et al, 2020a). If the fluid flow rate in tubing string changes significantly for certain factors and results in momentum conversion in these conditions, violent pressure fluctuations will be caused in tubing string (Li et al, 2013).…”
Section: Symbol Annotationsmentioning
confidence: 99%
“…They are tensile failure and shearing failure. The tensile failure was mainly caused by the drag force caused by the radius flow [9,10]. The higher the flow rate, the greater the drag force it will cause.…”
Section: Analysis Modelmentioning
confidence: 99%
“…Choking was shown to occur also in twodimensional flows when the acceleration effect is important. In a high-pressure gas well, Jin et al (2011aJin et al ( , 2012a showed that gas acceleration was important in the near-wellbore region and provided the critical bottom hole flowing pressure for the occurrence of a choked flow. So far, no one has studied the effect of acceleration on the gas production rate in a well intersected by a propped hydraulic fracture.…”
Section: Introductionmentioning
confidence: 98%